Epigenetic silencing of BCL6B inactivates p53 signaling and causes human hepatocellular carcinoma cell resist to 5-FU - Li, Xin (Oncotarget, 2015)
BCL6B is a potential tumor suppressor in human gastric cancer, but the regulation and mechanism of BCL6B in human hepatocellular carcinogenesis remain unclear. This study is to explore the epigenetic change and mechanism of BCL6B in human hepatocellular carcinoma (HCC). Nineteen hepatic cancer cell lines, 50 cases of adjacent tissue and 149 cases of HCC samples were employed. BCL6B is methylated in 100% (19/19) of human HCC cell lines, 40.0% (20/50) of adjacent tissue samples and 86.6% (129/149) of primary cancer samples. Methylation of BCL6B is associated with HBV positive (p < 0.05). But no association was found with age, sex, tumor size, differentiation, TNM stage, recurrence and survival. Loss of BCL6B expression was found in 19 of completely methylated HCC cell lines. BCL6B was re-expressed after 5-aza-2′-deoxycytidine treatment. Restoration of BCL6B expression suppressed cell proliferation, induced apoptosis and G1/S arrest in HCC cells. The expression of EGR1, a key component of p53 signaling, was increased after re-expression BCL6B in HCC cells. Re-expression of BCL6B activated p53 signaling and sensitized HCC cells to 5-fluorouracil. BCL6B is frequently methylated in human HCC and the expression of BCL6B is regulated by promoter region hypermethylation. BCL6B activates p53 signaling by increasing EGR1 expression in HCC.